HUBUNGAN ANTARA HIPERTENSI DENGAN KUALITAS HIDUP PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 3 - Putri Gina Nonlohi (2023)
Background: Cases of hypertension in the elderly occurred at the age of> 55 years in Indonesia in 2018. Elderly with hypertension have a lower quality of life. This is due to the aging process that occurs in the elderly which causes various kinds of health problems such as hypertension and also rheumatism. The higher the life expectancy of the elderly, the better the quality of life. Research Objectives: To determine the relationship between hypertension and the level of quality of life in the elderly. Research Methods: This study used a correlational quantitative research design with a cross-sectional approach. The sample in this study were 56 elderly people. In this study, univariate and bivariate tests were used using SPSS 25. Results: The results obtained for the highest hypertension scores were in the isolated systolic hypertension category with a percentage of 45.9% and the highest quality of life scores were in the poor quality of life category with a percentage of 41%. After the correlation test, it was found that there was a significant relationship between hypertension and quality of life, with p=0.004 and r=0.360 having positive values in the same direction. The conclusion of this study is that there is a significant relationship between hypertension and unidirectional quality of life.